Design Improvement of a Corndog MSME Worktable to Minimize MSDs Risk Using RULA and NBM Approaches - Nahdita Utomo; Agus Edy Pramono (Jurnal Sistem Teknik Industri, 2026)
This study aims to analyze the ergonomic conditions of a corndog workstation and propose an improved table design based on workers’ anthropometry. The research was conducted by direct observation, measurement of workstation dimensions and worker anthropometry, and posture assessment using the RULA method and Nordic Body Map (NBM) questionnaire. The results show that both workers obtained a RULA score of 5, indicating the need for further investigation and immediate improvements. The NBM results reveal discomfort in several body parts, including the neck, upper limbs, back, and wrists. Anthropometric analysis indicates a mismatch between table dimensions and workers’ elbow height and reach distance, particularly in terms of height and length. Based on these findings, a redesigned worktable with dimensions of 100 × 60 × 90 cm is proposed to better accommodate optimal reach zones and worker characteristics. This improvement is expected to reduce the risk of MSDs, enhance comfort, and improve work productivity. This study contributes by providing an integrated approach combining posture analysis, worker complaints, and anthropometry as a basis for ergonomic workstation design in MSMEs.